BALANCED MONETARY POLICY IN RUSSIA: MYTHS AND REALITY - A. E. Polonskiy (Финансы: теория и практика, 2017)
The article highlights the monetary policy’s role in creating conditions conducive to economic growth recovery and modernisation of the Russian economy. A review of different opinions shows what a balanced monetary policyshould be like in Russia. Russian scientific and business communities often express the following views on theBank of Russia’s role in the aforementioned processes: to switch to ‘quantitative easing’ policy, Russian style; to come back to a managed floating or pegged exchange rate of the ruble; to abandon ‘discretionary’ policy. The article emphasises that the central bank can influence the money supply dynamics only implicitly. That is why a considerable key rate reduction and excess money supply build up inflationary pressure, increase financial risks and destabilise the economic situation as a whole. Inflation may significantly lessen the impact of money supplyincrease on the economy’s monetisation. The article is sharply critical of the proposals to return to the policy of a pegged exchange rate of the ruble. Many countries’ experience suggests that given severe external shocks in the economy, which is largely dependent on the external economic environment, the support of the national currency exchange rate for a long period of time requires a sizeable amount of international reserves to be spent witheconomic imbalances keep rising. As a result, central banks will have to lower the exchange rate or release it. Thefloating exchange rate is an embedded economic stabiliser and makes it possible to offset an adverse impact ofexternal shocks. The Bank of Russia believes that its main contribution to the economic development is to reduce inflation and maintain it at a low level. The Bank of Russia seeks to pursue balanced monetary policy rather than ‘discretionary’ one, i. e. the policy, which implies only one goal for the central bank - low and stable inflation.However, this goal should be reached not in any way but taking into account Russian economic potential and the need to ensure financial stability.